Innovativeness of Banks and Insurance Companies in Developing Markets: Guidelines for Success - Mojca Nekrep (Naše gospodarstvo/Our economy, 2013)
The article examines innovation activities in banks and insurance companies in Slovenia’s developing financial market. The importance of the efficient new financial services development process and the impact of three core factors (i.e., marketing synergy, organizational culture, and market characteristics) on the services success are stressed. Market characteristics are the most important success factor of new banking and insurance services. The liberalization of financial markets in the European Union has led to a search for new opportunities of global financial corporations in less developed financial markets. The consequence of the increa- sed competition is the need for the innovation of domestic and conservative finan- cial organizations.